2017
DOI: 10.1563/aaid-joi-d-17-00108
|View full text |Cite
|
Sign up to set email alerts
|

Healing at the Interface Between Autologous Block Bone Grafts and Recipient Sites Using n-Butyl-2-Cyanoacrylate Adhesive as Fixation: Histomorphometric Study in Rabbits

Abstract: The aim of the present split-mouth (split-plot) study was to describe the sequential healing in the interface between autologous bone grafts and recipient parent bone, fixed using an n-butyl-2-cyanoacrylate adhesive with or without an additional titanium fixation screw. Bone grafts were collected from the calvaria and fixed to the lateral aspect of the mandible in 24 rabbits. The cortical layers of the recipient sites were perforated, and the grafts were randomly fixed using an n-butyl-2-cyanocrylate adhesive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In some instances, however, a gap was still present, occupied by connective tissue or cyanoacrylate. After 4 weeks of healing, the adhesive was degraded by about 62% compared the 2-week period of healing, corroborating the results from another study that showed that the major degradation of cyanoacrylates occurred during the first weeks of healing (De Santis, Silva, et al, 2017).…”
Section: New Mineralize Bone % Xenograftsupporting
confidence: 87%
See 1 more Smart Citation
“…In some instances, however, a gap was still present, occupied by connective tissue or cyanoacrylate. After 4 weeks of healing, the adhesive was degraded by about 62% compared the 2-week period of healing, corroborating the results from another study that showed that the major degradation of cyanoacrylates occurred during the first weeks of healing (De Santis, Silva, et al, 2017).…”
Section: New Mineralize Bone % Xenograftsupporting
confidence: 87%
“…Cyanoacrylates were used with positive results in experimental studies in rabbits (Salata et al, 2014;Xavier & Leite, 2015). However, other experimental studies reported better outcomes at grafts secured with screws compared to grafts secured with cyanoacrylate adhesive (Baş et al, 2012;De Santis, Silva, et al, 2017). In an experiment in rabbits (De Santis, Silva, et al, De Santis, Silva, et al, 2017), autogenous bone blocks were fixed to the lateral aspect of the mandible using an N-butyl-2-cyanocrylate adhesive, either with or without an additional fixation screw.…”
Section: Introductionmentioning
confidence: 99%
“…It was identified that the cyanoacrylate adhesive caused less inflammation and induced a higher mineralized tissue volume than the screw. However, a study in 24 rabbits with 40 days as an evaluation period, in which an adhesive of n-butyl-cyanoacrylate was applied to bond a block of autogenous bone graft to the lateral aspect of the mandible and then analyzed histomorphometrically, demonstrated that the bone graft was maintained fixed during the whole observation period (3-7-20-40 days) but this was not biologically incorporated into the recipient site [14]…”
Section: Introductionmentioning
confidence: 99%
“…Ideal adhesives could either be biologically inert or guide the healing response as with a tissue engineering approach [53]: the same biomechanical design principles apply to minimizing stress concentrations for tissue engineered biomaterials at interfaces between soft and hard tissues. Current adhesive approaches to orthopedic repair primarily use bone cements (e.g., [54]), cyanoacrylate- [55, 56, 57, 58, 59] or methacrylate-based chemistries [60, 61, 62, 63], which may be appropriate for fracture repair but are significantly more stiff than desirable for tendon-to-bone repair. Furthermore, biocompatibility is limited unless all free acrylate moieties are consumed.…”
Section: Discussionmentioning
confidence: 99%